Aplikasi AB Mix dan POC Limbah Pertanian terhadap Sawi Pagoda (Brassica narinosa L.) Hidroponik Sistem Wick - Kezia Maharani Hutajulu; Okti Herliana; Muhammad Bachtiar Mustafa; Tamad Tamad; Ni Wayan Anik Leana; Ahmad Fauzi (Vegetalika, 2025)
Hydroponic cultivation of pagoda mustard (Brassica narinosa L.) is a solution to increase production time efficiency and produce cleaner and more nutritious vegetables. However, the high price of AB mix fertilizer is an obstacle for hydroponic farmers, so alternative sources of nutrients are needed, such as Liquid Organic Fertilizer (LOF), which utilizes agricultural waste to make it more economical. This study was conducted from July to September 2024 at the screenhouse of the Experimental Farm of Jenderal Soedirman University, Purwokerto, using a Randomized Block Design (RBD) with two treatment factors: the first treatment was the concentration of AB Mix fertilizer (A), which consisted of four levels, namely A0 (0% AB Mix), A1 (25% AB Mix), A2 (AB Mix 50%), and A3 (AB Mix 100%). The second treatment was the concentration of POC (Liquid Organic Fertilizer) from agricultural waste (P) with three levels: P1 (POC 10 mL/L), P2 (POC 20 mL/L), and P3 (POC 30 mL/L). The data were analyzed using analysis of variance, followed by Duncan's Multiple Range Test (DMRT) at a 95% confidence level. The results showed that the 100% AB mix fertilizer concentration produced the highest results in terms of the number of leaves (up to 57), fresh plant weight (up to 92.22 g), dry plant weight (up to 7.35 g), and chlorophyll content (up to 20.73 mg/L). Substitution of agricultural waste POC increased the number of leaves by 2 leaves and fresh plant weight by 54.15 g at a concentration of 16.7 mL/L. The combination of 50% AB mix with 30 ml/L POC provided the best results in increasing nitrogen uptake, plant height, and leaf area.